COMMUNICATIVE ANALYSIS OF THE CREATIVE PROCESS IN ART COMMUNITIES - A. M. Pivovarov (Дискурс, 2016)
On the issue of identification of components of the creative process, the author proposes to rely on notions and concepts asserting the deep relationship between communication and creativity. The communicative approach involves revealing of sub-processes involved in creativity by analyzing communication that takes place in the team, whose members are engaged in solving a creative problem. For the analysis of the artistic creative process it is proposed to use a model, major components (sub-processes) of which include problem statement, emotional activation, generating, objectification and evaluating. The paper describes the sub-processes of objectification and excitement in individual and team work of artists, as well as a role performed by communication in each sub-process. The evidence-based framework for the paper included the data gathered with a method of a semi-structured interview collected during the field research. Their object included four art communities that had brought together more than thirty artists in an urban environment who work in various genres of the contemporary art.